NF-κB p65 directs sex-specific neuroprotection in human neurons. Issue 1 (December 2018) - Ruiz-Perera, Lucia; Schneider, Lennart; Windmöller, Beatrice; Müller, Janine; Greiner, Johannes; Kaltschmidt, Christian; Kaltschmidt, Barbara
Abstract Protection of neurons against oxidative stress is crucial during neuronal development, maintenance and for treating neurodegenerative diseases. However, little is known about the molecular mechanisms underlying sex-specific maturation and survival of neurons. In the present study, we demonstrate NF-κB-p65 mediated neuroprotection in human glutamatergic neurons differentiated from inferior turbinate stem cells (ITSCs) in a sex-dependent manner. We successfully differentiated ITSCs into MAP-2+ /NF200+ /Synaptophysin+ /vGlut2+ -glutamatergic neuronsin vitro andex vivo and validated their functionality. TNF-α-dependent NF-κB-p65 activation was accompanied by significant neuroprotection against oxidative stress-induced neuronal death, which was surprisingly higher in neurons from female donors. Accordingly, sex-specific neuroprotection of female neurons was followed by an increased expression of special NF-κB target genes SOD2 and IGF2. Among these, SOD2 is a well known gene protecting cells against oxidative stress resulting in longevity. In addition, IGF2 is known to promote synapse formation and spine maturation, and it has antioxidant and neuroprotective effects against oxidative damage. In conclusion, we show that NF-κB-p65 is a key player in neuroprotection of human neurons, however the protective gene expression program beneath it differs between sexes. Our findings are in accordance with the increasing evidences pointing towards sex-specific differences in risk and severity of neurodegenerative diseases.